2015
DOI: 10.1007/s11664-015-4032-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, Thermal, and Magnetic Characterization of Natural Tetrahedrites–Tennantites of Different Origin

Abstract: Naturally occurring sulfosalt minerals of the tetrahedrite-tennantite series ((Cu,Fe,Zn,Ag,Hg) 12 (Sb,As) 4 S 13 ) are studied because of their potential use as basic components in the manufacture of thermoelectric devices for moderatetemperature applications. In the work reported herein, the chemical, crystallographic, thermoelectric, and magnetic properties of four specimens from different ores from Europe and America were exhaustively characterized. Our study revealed that these natural tetrahedrites usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…The reported χ value for Cu 12 Sb 4 S 13 at low temperature (T < 25 K), was a bit larger than the value for Cu 12 Sb 4 S 13 reported in the literature [12] (0.0041 emu/mol), [30] (less than 0.001 emu/mol) and [18] at 2 K but was similar to χ values of natural tetrahedrite-tennantite (above 0.15 emu/mol) [15]. It might be attributed to Fe impurities.…”
Section: Magnetization and Heat Capacity Of Synthetic Cu 12 Sb 4 S 13contrasting
confidence: 43%
See 2 more Smart Citations
“…The reported χ value for Cu 12 Sb 4 S 13 at low temperature (T < 25 K), was a bit larger than the value for Cu 12 Sb 4 S 13 reported in the literature [12] (0.0041 emu/mol), [30] (less than 0.001 emu/mol) and [18] at 2 K but was similar to χ values of natural tetrahedrite-tennantite (above 0.15 emu/mol) [15]. It might be attributed to Fe impurities.…”
Section: Magnetization and Heat Capacity Of Synthetic Cu 12 Sb 4 S 13contrasting
confidence: 43%
“…For Cu 12 Sb 4 S 13 and Cu 11.9 Sb 4 S 13 , both C and θ are smaller, which is related to the valence of Fe ion ( Table 1). The influence of Fe content on χ and θ depends on the Fe valence (antiferromagnetic for Fe 2+ ions) in the natural tetrahedrites [15,31].…”
Section: Magnetization and Heat Capacity Of Synthetic Cu 12 Sb 4 S 13mentioning
confidence: 99%
See 1 more Smart Citation
“…13,[56][57][58] It should be noted that the natural minerals showed rather low ZT's due to excessive ρ. 13,59 For Cu 12−x Tr x Sb 4 S 13 , various synthesis techniques have been examined for large-scale TE application. 50,58,[60][61][62] The Te substituted system Cu 12 Sb 4−x Te x S 13 (0 ≤ x ≤ 1) has also been examined.…”
Section: Tetrahedrite (P-type)mentioning
confidence: 99%
“…Further investigations aiming at determining the inluence on the chemical composition of the mineral on the thermoelectric properties will be interesting to undertake. In this regard, a preliminary study carried out on minerals from various geographical origins has shown that all of them show semiconducting-like properties despite diferences in their chemical composition [51].…”
Section: Scaling Up Tetrahedrite Synthesismentioning
confidence: 99%